Policies "Establishing National Relief and Response System" - سعيد علي; بعيرة انس (Dirasat in Economics and Business, 2007)
The aim of this paper is to examine the management of Libyan humanitarian policies as part of the growing interest in the study of public policy. It focuses on: The definition and principles of humanitarian assistance. The legal and institutional Framework related to the Management of humanitarian work in Libya. The future of the management of humanitarian work in Libya. Finally, the paper recommends few steps to improve the management of humanitarian policies in Libya.